2018
DOI: 10.1159/000487388
|View full text |Cite
|
Sign up to set email alerts
|

Update on Vitamin E and Its Potential Role in Preventing or Treating Bronchopulmonary Dysplasia

Abstract: Vitamin E is obtained only through the diet and has a number of important biological activities, including functioning as an antioxidant. Evidence that free radicals may contribute to pathological processes such as bronchopulmonary dysplasia (BPD), a disease of prematurity associated with increased lung injury, inflammation and oxidative stress, led to trials of the antioxidant vitamin E (α-tocopherol) to prevent BPD with variable results. These trials were all conducted at supraphysiologic doses and 2 of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 113 publications
3
27
0
1
Order By: Relevance
“…Unfortunately, until now, clinical studies aimed at reducing the frequency of BPD by the supplementation of vitamin E have not brought the expected favorable results [33]. Our finding may support the idea of re-reviewing the hitherto knowledge about the connection between vitamin E and BPD, and the possible methods of preventing or alleviating this severe complication of prematurity, by obtaining the adequate level of appropriate isoform of this antioxidant in the maternal/infant organism [34]. We also believe that it is worth investigating whether the lower level of vitamin E carrier proteins might decrease the bioavailability of vitamin E, despite supplementation.…”
Section: Discussionsupporting
confidence: 60%
“…Unfortunately, until now, clinical studies aimed at reducing the frequency of BPD by the supplementation of vitamin E have not brought the expected favorable results [33]. Our finding may support the idea of re-reviewing the hitherto knowledge about the connection between vitamin E and BPD, and the possible methods of preventing or alleviating this severe complication of prematurity, by obtaining the adequate level of appropriate isoform of this antioxidant in the maternal/infant organism [34]. We also believe that it is worth investigating whether the lower level of vitamin E carrier proteins might decrease the bioavailability of vitamin E, despite supplementation.…”
Section: Discussionsupporting
confidence: 60%
“…Polarity may be involved because α-tocopherol possessing lower polarity indicated bigger decreases than γ-tocopherol over lactation. As positive roles have been attributed to α-tocopherol in bronchopulmonary dysplasia and childhood asthma, γ-tocopherol indicates more harmful effects through pro-inflammatory properties than its antioxidant benefits (19) . However, infant formulas, calculated by the published data, provide a much lower ratio of α-:γ-tocopherol as (0•68-2•51):1 (4,10) .…”
Section: Tocopherols and Carotenoidsmentioning
confidence: 99%
“…Other vitamin E isoforms were less investigated, but concerns have arisen that an increasing number of foods and formulas deliver much higher γ-tocopherol than α-tocopherol (4,16,17) . γ-Tocopherol also decreases lipid peroxidation (weaker than α-tocopherol) and neutrophilic inflammation (stronger than α-tocopherol), but it can promote type 2 inflammation (18,19) . The latest early life study in both Nigerian and American maternal-neonatal dyads reported the association between decreased circulating α-:γ-tocopherol and negative birth outcomes such as Caesarian sections (20) .…”
mentioning
confidence: 99%
“…However, none of these trials were conducted after 1991, and the nature and epidemiology of BPD has since profoundly evolved. No human trial has investigated antenatal supplementation and neonatal outcomes so far (for review, see [61]).…”
Section: Micronutrientsmentioning
confidence: 99%